Hoaks and Resistance to Government Motion Case Study KAMI (Koalisi Aksi Menyelamatkan Indonesia) - Fera Belinda; Maria Puspitasari (Journal of Social Science, 2021)
oaks or fake news is a serious concern because it has a negative impact due to information that is not ascertained the truth. Especially during the political year of the 2019 presidential election, the spread of hoaxes is increasingly massively attacking each candidate personally and institutionally. The Ministry of Communication and Information recorded in 2018 there were 733 hoaks content. In 2019, hoax content increased sharply to 3,801. The drastic increase in the amount of hoax content occurred from February to May, along with the 2019 elections. Not stopping in the 2019 presidential election, until the first half of 2020, the number of hoaks content has reached 1855. The number of hoaks content increased again in March, along with the emergence of the Covid-19 pandemic in Indonesia and continued with the enactment of the Omnibus Law Ciptakerja. The development of social media technology and smartphones is one of the causes of the current hoaks outbreak. The theories used in this study are the concept of hoaxes, social media and the firehose of falsehood, as well as the theory of delegitimization. The focus of the research on youtube social media channel contains a statement from the Indonesian Rescue Action Coalition Movement (KAMI) in the period September – October 2020. Although it is a new group, us members are old figures who have been known to be opposed to the Jokowi government. The research methodology used is qualitative approach with data collection method through observation of video text posted. While the method of data analysis is done by analyzing the content or content to give an idea of the rush of fake news that has the potential to harm threats that can disrupt security stability, can even potentially damage the joints of national and state life, as well as become a threat to the sustainability of democracy. The results of this study concluded that hoaxes are usually chained and re-forward existing information and that the content has similarities to previous hoax content. This study recommends the government to actively educate the public regarding media literacy to be selective in receiving messages.